Uncovering the Secrets Behind Enumeration Rules: The Art of Combinatorics Thinking - Bilkis, Cahaya; Martini; Muchamad Subali Noto; Irmawati Liliyana Kusuma Dewi (International Journal of Educational Research Excellence (IJERE), 2024)
This research aims to analyze students' combinatorial thinking skills after using learning worksheets on enumeration rules. This research aims to provide solutions by applying learning materials to improve students' combinatorial thinking skills in solving math problems. The research method used is qualitative research. The research technique in this case is to use data triangulation. The purpose of triangulation is to increase the validity and reliability of research findings by confirming or complementing findings from various sources or perspectives. The results in this study are the diversity of the fulfillment of indicators in the ability to think combinatorics, including students with the S-1 category can fulfill all indicators of combinatorics thinking ability. Students in the S-2 category only fulfill 1 indicator of combinatorics thinking ability. Students in the S-3 category could not fulfill all the indicators of combinatorics thinking ability.